PEMBERDAYAAN MASYARAKAT DALAM PELESTARIAN MASAKAN TRADISIONAL NUSANTARA - Afrizal Afrizal; Emilia Susanti; Nurdiana Nurdiana; Roswati Roswati; Wardani Purnama Sari (XXXXX, 2022)
Indonesian traditional cuisine is one of the nation's wealth that must be preserved. Considering of foreign cuisine development which is more compatible with the tastes of the Indonesian people, especially the current millennial generation. The purpose of this community service is to give training to the community in preserving the Indonesian traditional cuisine and to give an understanding to the community of the importance of preserving traditional cuisine, especially pempek, in increasing communities’ income. The methods used in this activity were the lecturing and practicing method. As a result of this community service, the participants seemed enthusiastic in participating in each stage of the activity and hoped that activities could continue to increase knowledge and family income.